(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
This article explores the implementation of group learning methods in teaching English, highlighting the benefits and strategies for effective implementation. It emphasizes the significance of collaborative learning in fostering language proficiency, communication skills, and cultural understanding among learners. The article also presents key keywords such as group learning, English language education, collaboration, communication skills, and cultural understanding.